2009
DOI: 10.1094/ats-2009-0724-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Late Fall Sod Installation Produces Equivalent or Greater Rooting Strength ofPoa pratensisThan Typical Spring Installations During the Subsequent Growing Season

Abstract: Securing adequate time for proper turfgrass establishment following athletic field construction or renovation is a significant challenge. Spring construction and renovation projects often get delayed thereby diminishing the necessary time for sufficient root development before anticipated athletic field use. An alternative sod installation timing following fall sports may provide adequate root development during a typical period of minimal to no field usage. Five sod installation treatments (December covered, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…King and Beard (1969) found athletic fields may not perform adequately if sods used to establish the fields have inadequate root systems. Dormant sodding in December has been found to be advantageous for developing superior root strength in cool season species, such as Kentucky bluegrass ( Poa pratensis L.), when compared with a traditional sodding in May (Henderson et al, 2009). In our study, mid‐March propagation resulted in higher RLD compared with mid‐June propagation (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…King and Beard (1969) found athletic fields may not perform adequately if sods used to establish the fields have inadequate root systems. Dormant sodding in December has been found to be advantageous for developing superior root strength in cool season species, such as Kentucky bluegrass ( Poa pratensis L.), when compared with a traditional sodding in May (Henderson et al, 2009). In our study, mid‐March propagation resulted in higher RLD compared with mid‐June propagation (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research conducted by King and Beard (1969) also reported the influence of soil texture on sod rooting, with sod transplanted on organic soil producing greater rooting than sod transplanted on a mineral soil. Henderson et al (2009) studied the effect of the timing of Kentucky bluegrass sod installation on sod rooting strength. In their study, sod rooting was measured as the lifting force required to detach the sod from the underlying soil using a digital force gauge.…”
Section: The Effect Of Wear and Soil Compaction On Kentucky Bluegrassmentioning
confidence: 99%
“…Sod rooting strength was measured using a digital force gauge. During initial planting, sod was placed in a 15-cm diameter frame (rooting box) with a piece of wire mesh attached to the bottom, as described by Henderson et al (2009). Uniform tension was applied to the frame at a constant rate until the sod detached free from the soil with the maximum force recorded.…”
Section: Wear and Recoverymentioning
confidence: 99%
“…A juvenile grass often requires 12–18 mo on organic soils and 21–24 mo on mineral soils to reach maturity for a safe playing surface (Li, Fang, & Han, 2011; Shearman et al., 2001). A re‐sodded surface may take 3–6 mo before it is ready for play (Henderson, Miller, Guillard, Harel, & Raman, 2009). Washed sod is the quickest establishment method which provides an opportunity for deep root growth and the prevention of weed infestations during the establishment period, as compared to other methods including direct seeding, juvenile sod, or unwashed sod (Canaway, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A juvenile grass would need 12 to months on organic soils and 21 to 24 months on mineral soils to reach maturity for a safe playing surface (Rieke and Beard, 1969;Shearman et al, 2001;Li et al, 2011). Re-sodding the surface may take 3 to 6 months for a well-rooted turf field to be ready for games (Henderson et al, 2009). Washed sod (removing the existing soil from the sod by high-pressure water) is the quickest establishment method and a way to avoid soil layering problems.…”
Section: Introductionmentioning
confidence: 99%